Developing A Model of HOTS Questions for Narrative Reading Text for IX Grade Students of SMPN 2 Jorong - Evelyn Simanjuntak; Wahyuningsih Usidiati; Elanneri Karani (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan Indonesia (IATPI), 2020)
Teachers are required to have good reading material with various questions exercises to meet students’ interest to improve their reading ability. This developmental research was undertaken to develop a model of instructional material of HOTS questions for narrative reading texts for IX grade students of SMPN 2 Jorong. The development of the model in R & D research involved the following framework: needs assessment, reference study, material development, expert validation, tryout, revision, and final product. The subject of the research was the students of grade IX of SMPN 2 Jorong. The instruments used were observation sheet, questionnaire sheet, students’ test result, and validity and advisability test sheet to take the data. The final product was a Model of HOTS Questions For Narrative Reading Text in the form of instructional material consisting of Cover; Introduction, and Content. The content of the product consisted of 2 Units that contain narrative reading texts with the titles Hansel and Grethel, Malin Kundang, and Rapunzel. Each story was inserted with HOTS questions to ask the students to generalise, to analyse, to compare, to distinguish, and to correlate. Based on the result, the model of HOTS questions was efficient and advisable to be implemented.